# Simplify secA(1 –

By trigonometric identities, sec A = 1/cos A & tan A = sin A/cos A

Using these identities, we have

sec A (1 – sin A)(sec A + tan A) = sec A (1 – sin A)(sec A + tan A) = sec A (1 – sin A)(sec A + tan A) = sec A (1 – sin A)(sec A + tan A) = sec A (1 – sin A)(sec A + tan A) = [, sin2 A + cos2 A = 1 cos2 A = 1 – sin2 A]

sec A (1 – sin A)(sec A + tan A) = 1

Thus, sec A (1 – sin A)(sec A + tan A) = 1.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Trigonometric Identities39 mins  Heights and Distances-I45 mins  Trigonometric Identities-II43 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Evaluate

<
AP- Mathematics

If tan A = cot B AP- Mathematics

Evaluate

<
AP- Mathematics

Evaluate

<
AP- Mathematics

Show that

AP- Mathematics

Evaluate sin 60° AP- Mathematics

In right angle isAP- Mathematics

Is it right to saAP- Mathematics

Show that

AP- Mathematics

Is it right to saAP- Mathematics